2014
DOI: 10.5194/acp-14-8089-2014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and elevational variations of black carbon and dust in snow and ice in the Solu-Khumbu, Nepal and estimated radiative forcings

Abstract: Abstract. Black carbon (BC) and dust deposited on snow and glacier surfaces can reduce the surface albedo, accelerate snow and ice melt, and trigger albedo feedback. Assessing BC and dust concentrations in snow and ice in the Himalaya is of interest because this region borders large BC and dust sources, and seasonal snow and glacier ice in this region are an important source of water resources. Snow and ice samples were collected from crevasse profiles and snow pits at elevations between 5400 and 6400 m a.s.l.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
2

Year Published

2015
2015
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 72 publications
6
150
2
Order By: Relevance
“…Based on a 10-year record of mineral dust and BC concentrations, retrieved from an ice core at Mera Peak, Nepalese Himalaya, Ginot et al (2014) found that lightabsorbing particulates cause up to 26 % of the total annual surface melting. Another study performed at Mera Peak shows that mineral dust dominates absorption and may reduce the albedo of snow by up to 40 % (Kaspari et al, 2014). Investigations for the Colorado River basin, western US, show that the radiative forcing of mineral dust deposition may shorten the duration of snow cover by several weeks (Skiles et al, 2012) and also affects the timing and magnitude of runoff (Painter et al, 2010).…”
Section: J Gabbi Et Al: Impact Of Saharan Dust and Black Carbon On mentioning
confidence: 99%
See 3 more Smart Citations
“…Based on a 10-year record of mineral dust and BC concentrations, retrieved from an ice core at Mera Peak, Nepalese Himalaya, Ginot et al (2014) found that lightabsorbing particulates cause up to 26 % of the total annual surface melting. Another study performed at Mera Peak shows that mineral dust dominates absorption and may reduce the albedo of snow by up to 40 % (Kaspari et al, 2014). Investigations for the Colorado River basin, western US, show that the radiative forcing of mineral dust deposition may shorten the duration of snow cover by several weeks (Skiles et al, 2012) and also affects the timing and magnitude of runoff (Painter et al, 2010).…”
Section: J Gabbi Et Al: Impact Of Saharan Dust and Black Carbon On mentioning
confidence: 99%
“…Kaspari et al (2014) determined light absorption of mineral dust in snow and ice of a Himalayan glacier based on gravimetrically determined Fe concentrations. Accordingly, we used records of iron (Fe), provided by the ice core, to infer mineral dust concentrations.…”
Section: Mineral Dustmentioning
confidence: 99%
See 2 more Smart Citations
“…During the cold and dry winter season, haze (heavily loaded with carbonaceous aerosols) builds up over South Asia, and exerts profound influences on regional radiative forcing Ramanathan and Carmichael, 2008), hydrologic cycles (Menon et al, 2002;Ramanathan et al, 2005), and likely Himalaya-Tibetan glacier melting that could be accelerated by the absorption of sunlight induced by BC in the air and deposited on the ice and snow surfaces Hansen and Nazarenko, 2004), although BC deposited in snow and glaciers at some locations may not significantly affect the energy balance Kaspari et al, 2014).…”
mentioning
confidence: 99%